Gender-specific substance use patterns and associations with individual, family, peer, and school factors in 15-year-old Portuguese adolescents: a latent class regression analysis - João Picoito; Constança Santos; Isabel Loureiro; Pedro Aguiar; Carla Nunes (BMC, 2019)
Abstract Background Adolescence is a critical period of vulnerability to substance use. Recent research has shown that gender differences in adolescence substance use are complex and in constant flux. The present study aims to investigate gender differences in substance use and initiation patterns in male and female adolescents, and to assess individual, family, peer, and school associated factors of these patterns. Methods We applied latent class regression analysis to a Portuguese representative population sample of 1551 15-year-old adolescents, drawn from the 2010 'Health Behavior in School-Aged Children' survey, to characterise different profiles of substance use and initiation for boys and girls, and to identify factors associated with latent class membership, stratifying the associations analysis by gender. Results Three common classes were found for both genders, specifically, Non-Users (boys [B] 34.42%, girls [G] 26.79%), Alcohol Experimenters (B 38.79%, G 43.98%) and Alcohol and Tobacco Frequent Users (B 21.31%, G 10.36%), with two additional unique classes: Alcohol Experimenters and Tobacco Users in girls (18.87%), and Early Initiation and Poly-Substance Users in boys (5.48%). Poor school satisfaction, bullying, fighting and higher family affluence scale score formed a common core of associated factors of substance use, although we found gender differences in these associations. In girls, but not in boys, family factors were associated with more problematic substance use. Not living with both parents was associated with girl's Alcohol and Tobacco Frequent Users (gATFU) class (OR 3.78 CI 1.18-12.11) and Alcohol Experimenters and Tobacco Users (AETU) class (OR 3.22 CI 1.4-7.44). Poor communication with mother was also associated with gATFU class membership (OR 3.82 CI 1.26-11.53) and AETU class (OR 3.66 CI 1.99-6.75). Additionally, a higher psychological symptoms score was associated with gATFU class membership (OR 1.16 CI 1.02-1.31). Conclusion Although we found common patterns and associated factors between boys and girls, we report two unique patterns of substance use in boys and girls and specific associations between family, school and peers, and individual factors with these patterns. These findings underscore the need for substance use prevention and health promotion programmes that address potential differences in substance use patterns and associated factors.